Bertani Padi Bagi Orang Melayu Sambas: Kearifan Lokal, Nilai-Nilai Islam, dan Character Building - Kurniawan, Syamsul - (Universitas Islam Negeri Raden Intan Lampung, 2018)
Farming is the local wisdom of the Sambas Malays, which has a very strategic role in building character, especially for farmers. The values in the local “farming” wisdom adopted by the Sambas Malays will be an identity for them, their mark as Muslims and part of a community of dignified Malays. This is in line with opinion of Hermansyah (2015), who calls Melayu is identic with Islam. The focus of this article is how the Sambas Malays builds character through farming with various representative forms. The article departed from qualitative study in which the data was obtained from observation and in-depth interview at the research site, acquired conclusion that farming builds Islamic values in the Sambas Malays such as work ethic, responsibility, helping each other, sincerity, patience, generosity and caring.